2020
DOI: 10.1039/d0ta05137c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of A-site deficiency in layered perovskites: promotion of dual reaction kinetics for water oxidation and oxygen reduction in protonic ceramic electrochemical cells

Abstract: An A-site deficient layered perovskite PBCC95 is developed as a new oxygen electrode incorporated into a protonic ceramic electrochemical cell. The cell presents superior electrochemical performances and it can reversibly work between the electrolysis and fuel cell mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…35 Copyright 2020 American Chemical Society | 11 SU and HU of the conductivity and sinterability in comparison with the Ce-rich case. 32,[40][41][42] To further improve the stability of the Ba-based proton conductor, Murphy et al proposed the replacement of zirconium in BZCYYb with hafnium (Hf) to form BaHf x Ce 0.8x Y 0.1 Yb 0.1 O 3−δ (BHCYYb). 43 The BaHfO 3 has a higher Gibbs free energy for the reaction with H 2 O and CO 2 than BaZrO 3 , suggesting potentially higher chemical stability (Figure 5A).…”
Section: At a High Steam Concentration The Proton Oh ⋅mentioning
confidence: 99%
“…35 Copyright 2020 American Chemical Society | 11 SU and HU of the conductivity and sinterability in comparison with the Ce-rich case. 32,[40][41][42] To further improve the stability of the Ba-based proton conductor, Murphy et al proposed the replacement of zirconium in BZCYYb with hafnium (Hf) to form BaHf x Ce 0.8x Y 0.1 Yb 0.1 O 3−δ (BHCYYb). 43 The BaHfO 3 has a higher Gibbs free energy for the reaction with H 2 O and CO 2 than BaZrO 3 , suggesting potentially higher chemical stability (Figure 5A).…”
Section: At a High Steam Concentration The Proton Oh ⋅mentioning
confidence: 99%
“…Wang et al [108] reported a Pr 2 BaNiMnO 7−δ cathode that showed excellent compatibility with BCZYYb7111 electrolyte and generated a remarkable MPD of 1.07 W•cm −2 at 700 • C with almost negligible degradation after 100 h. The role of the effect of A-site cation ordering on the cathode performance and chemical stability in double perovskites is investigated for A-site cation-ordered LaBaCo2O5+δ and -disordered La0.5Ba0.5CoO3−δ by Bernuy-López et al [104], observing that A-site cation ordering leads to a higher oxygen-vacancy concentration, which explains the better electrochemical performance of LaBaCo2O5+δ compared to the disordered phase. An A-sitedeficient, layered perovskite, (PrBa0.8Ca0.2)0.95Co2O6−δ, was developed as an oxygen electrode for a reversible protonic ceramic cell where current density reached −0.72 A•cm −2 at 1.3 V, and a peak power density of 0.540 W•cm −2 was obtained at 600 °C in electrolysis and fuel-cell mode, respectively, which were much higher values than the A-site stoichiometric analogue [105]. A-site deficiency is generally recognized to improve the chemical stability of perovskite oxides and may also increase the oxide-ion-vacancy concentration and thereby the electrochemical performance.…”
Section: Triple Proton Oxide Ion Electron Hole-conducting Oxidesmentioning
confidence: 99%
“…BCZFY was chosen as the cathode in the development of a manufacturing cost model to estimate the production costs of PCFC stack technology using high-volume manufacturing processes [117]. As is the case for double perovskites [105], A-site deficiency in BCFZY increases oxygen deficiency, significantly improving oxygen diffusion and hydration kinetics: an MPD of 0.797 W•cm −2 was achieved at 650 • C for the composition Ba 0.9 Co 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 3−δ [118]. B-site deficiency in BCZFY is also reported to enhance performance with a cell containing a Ba(Co 0.…”
Section: Triple Proton Oxide Ion Electron Hole-conducting Oxidesmentioning
confidence: 99%
“…A twin-perovskite nanocomposite cathode(TPNCC) comprising PC and MIEC nano phases with Ba–Ce–Fe–Co–O of one-pot synthesis was proposed by Zhao et al, the effects of which on the texture properties of the Ba–Ce–Fe–Co–O (BCFC) TPNCC open a new opportunity toward high-performance protonic ceramic fuel cells (PCFCs) [ 67 ]. Tang et al developed a site-deficient layered perovskite (PrBa 0.8 Ca 0.2 ) 0.95 Co 2 O 6−δ , which indicates that the O 2 vacancies preferentially aligned as pairs in the directions as the degree of nonstoichiometry increased; this played a central role in promoting the macroscopically observed ionic conductivity of (PrBa 0.8 Ca 0.2 ) 0.95 Co 2 O 6−δ (PBCC95) [ 68 ]. Mahimai et al distinguished the novelty of barium strontium titanium oxide (BSTO),an attractive perovskite inorganic filler/ sulfonated poly (ether ketone) (SPEEK), polymer membrane efficiency, and adsorption strength of the membrane due to its crystalline structure, which led to high conductivity and stability [ 69 ].…”
Section: Application Of Perovskite-based Nanocomposites In Fuel Cellsmentioning
confidence: 99%
“…Facile composite membranes consisting of SPEEK/poly (amide imide) (PAI) and SrTiO 3 -based nanocomposite electrolyte were prepared by a solvent-casting technique to exploit the combined network of SPEEK, PAI, and SrTiO 3 , owing to polymer matric of stability criteria on hydrogen bonding and excellent proton conductor, as well as being hydrophilic in nature. This offers enhanced stability and the ability to fine-tune proton conductivity in the existence of PAI and SrTiO 3 [ 68 , 70 ]. Yavari et al synthesized a PtNP–CNTs–NdFeO3NPs–CH nanocomposite in a direct methanol fuel cell (DMFC) with perovskite oxide, which exposed the multifunctional energy harvesting using a single engineered material [ 71 ].…”
Section: Application Of Perovskite-based Nanocomposites In Fuel Cellsmentioning
confidence: 99%